Antimicrobial and Antioxidant Electrospun Membrane Incorporating Silver and Copper Complexes of Phenylboronic Acid-Functionalized 4,5-Diazafluorene Ligand - Kaya, Secil; Cebeci, Caner; Hancer, Hande; Akgul, Busra; Erden, Ibrahim; Ozbek, Tulin; Abamor, Emrah Sefik; Acar, Serap (WILEY-V C H VERLAG GMBH, 2025)
Thermally crosslinked polyacrylic acid (PAA)-polyvinyl alcohol (PVA) nanofibrous (NFC) membranes were developed via electrospinning for potential wound dressing applications with antioxidant and antimicrobial properties. Silver and copper complexes (AgSK and CuSK) of a phenylboronic acid-functionalized 4,5-diazafluorene ligand (SK) were synthesized, characterized, and incorporated into the membranes. SEM imaging revealed uniform, bead-free nanofibers with an average diameter of 725.35 +/- 173.79 nm. FTIR analysis confirmed the successful incorporation of compounds through characteristic C & boxH;N stretching bands at 1620-1630 cm(-1). DPPH assay showed that SK, AgSK, and CuSK exhibited antioxidant activities of 54.6 +/- 2.5%, 88.4 +/- 3.5%, and 79.6 +/- 3.4% at 90 min, respectively. Incorporation into the nanofibers did not significantly alter antioxidant performance. Antimicrobial activity was assessed against Escherichia coli, Staphylococcus aureus, and Candida albicans. AgSK showed the strongest inhibition, with MIC values of 62.5, 31.25, and 125 mu g/mL, respectively. AgSK-loaded membranes (AgSK-NFC) demonstrate antimicrobial activity with > 98% reduction in all tested strains. Biocompatibility tests with L929 fibroblasts showed improved cell viability upon membrane incorporation. The membranes also exhibited high swelling capacity, good water resistance, and sustained release over 7 days. With this study, for the first time, the use of 4,5-diazafluorene and its metal complexes in nanofibrous membranes has been demonstrated. Thus, an interdisciplinary approach combining materials science and coordination chemistry is established, broadening the scope for future developments in nanofiber-based technologies.
Keywords: 4,5-diazafluorene ligand; biological activity; electrospun nanofibrous membrane; metal complexes; phenylboronic acid; NANOFIBERS; DNA; DERIVATIVES; PYRIDINE; Pharmacology & Pharmacy; Chemistry